Morphology of dentition in Polish children with trisomy 21 (Down syndrome) - Żądzińska, Elżbieta; Lubowiedzka, Beata; Wochna-Sobańska, Magdalena (Anthropological Review, 2010)
This paper compares the dimensions and non-metric dental traits between Down syndrome patients (DS) and a control group. A total of 1,210 teeth of subjects with Down syndrome (diagnosed as regular trisomy 21 type) were analyzed. The mesiodistal (MD) and labiolingual or buccolingual (BL) diameters of each dental crown were measured, and the selected non-metric dental traits evaluated. The teeth of male and female DS patients were found to have lower values of both measurements compared to controls (excepting for the mesiodistal diameter of the lower mandibular premolar both in males and females). Sexual dimorphism of dental crown dimensions characteristic of contemporary human populations (the highest M-F difference was lower than 6%) was also observed: boys' teeth, particularly canines, are bigger than girls' (2.33 on average). Disorders in maxillary tooth alignment and the faint shoveling of upper central incisors (grade 1 according to ASU scale) were noted significantly more often among Down syndrome patients, but descriptive features correlating with dental crown size were observed more rarely (e.g., the distal accessory ridge on the upper canine and tuberculum Carabelli on the first molar).